TIP peptide inhalation in oleic acid-induced experimental lung injury: a post-hoc comparison - Hartmann, Erik K (BioMed Central, 2013)
BACKGROUND: The lectin-like domain of TNF-α mimicked by an inhaled TIP peptide represents a novel approach to attenuate a pulmonary edema in respiratory failure, which is on the threshold to clinical application. In extension to a previously published study, which reported an improved pulmonary function following TIP peptide inhalation in a porcine model of lavage-induced lung injury, a post-hoc comparison to additional experiments was conducted. This analysis addresses the hypothesis that oleic acid injection-induced capillary leakage and alveolar necrosis blunts the previously reported beneficial effects of TIP peptide inhalation in a porcine model. FINDINGS: Following animal care committee approval lung injury was induced by oleic acid injection in six pigs with a setting strictly according to a previously published protocol that was used for lung-lavaged pigs. Ventilation/perfusion-distribution by multiple inert gas elimination, parameters of gas exchange and pulmonary edema were assessed as surrogates of the pulmonary function. A significantly improved ventilation/perfusion-distribution following TIP inhalation was recognized only in the bronchoalveolar lavage model but not following oleic acid injection. The time course after oleic acid injection yielded no comparable impact of the TIP peptide on gas exchange and edema formation. CONCLUSIONS: Reported beneficial effects of the TIP peptide on gas exchange and pulmonary edema were not reproducible in the oleic acid injection model. This analysis assumes that sustained alveolar epithelial necrosis as induced by oleic acid injection may inhibit the TIP-induced edema resolution. Regarding the on-going clinical development of the TIP peptide this approach should hardly be effective in states of severe alveolar epithelial damage.